2008
DOI: 10.1175/2007mwr2029.1
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Mixed Physics versus Perturbed Initial/Lateral Boundary Conditions to Ensemble-Based Precipitation Forecast Skill

Abstract: An experiment is described that is designed to examine the contributions of model, initial condition (IC), and lateral boundary condition (LBC) errors to the spread and skill of precipitation forecasts from two regional eight-member 15-km grid-spacing Weather Research and Forecasting (WRF) ensembles covering a 1575 km X 1800 km domain. It is widely recognized that a skillful ensemble [i.e., an ensemble with a probability distribution function (PDF) that generates forecast probabilities with high resolution and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
71
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 44 publications
(74 reference statements)
8
71
0
1
Order By: Relevance
“…However, with the increasing use of ensembles at fine grid scales (e.g., Xue et al 2007;Clark et al 2009), an incentive exists to determine the best ways of using these techniques to both evaluate and provide better forecast guidance from ensemble forecasts, beyond simple application of the object-based methods to the ensemble mean forecast. Traditional spread and skill measures applied to ensembles, such as variance or mean squared error (MSE) of the ensemble mean, are affected by both bias and small displacements that can complicate interpretation in a manner similar to that with traditional verification measures applied to deterministic forecasts.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the increasing use of ensembles at fine grid scales (e.g., Xue et al 2007;Clark et al 2009), an incentive exists to determine the best ways of using these techniques to both evaluate and provide better forecast guidance from ensemble forecasts, beyond simple application of the object-based methods to the ensemble mean forecast. Traditional spread and skill measures applied to ensembles, such as variance or mean squared error (MSE) of the ensemble mean, are affected by both bias and small displacements that can complicate interpretation in a manner similar to that with traditional verification measures applied to deterministic forecasts.…”
Section: Introductionmentioning
confidence: 99%
“…One method commonly used to gain information about ensemble spread is to isolate the error sources by using different perturbation strategies for a set of forecasts (e.g., Houtekamer et al 1996;Stensrud et al 2000;Clark et al 2008). For example, to isolate model errors, the ''perfect analysis'' assumption can be used, in which identical sets of ICs/LBCs are used to initialize various ensemble members with mixed physics.…”
Section: Introductionmentioning
confidence: 99%
“…Clark et al (2008) found among other results that the ensemble variance in their MPP ensemble was greater than that in a PIC ensemble during the first 24 h of the forecast. In another experiment comparing MPP and a stochastic kinetic-energy backscatter scheme, Berner et al (2011) argued for a combination of both approaches.…”
Section: Introductionmentioning
confidence: 70%